The Roles Of Sulūk In Spiritual Empowerment Of Woman Practitioners In Institut Latihan Ilmu Tarekat (Ilit) Manarah - Nur Izzati Nadia binti Mohd Dzolkifli
The practice of sulūk is a practice that is familiar to the practitioners of the tasawwuf sect, especially to the followers of the Tarekat Naqsyabandiyyah Khalidiyyah. This practice has been inherited hereditarily from the previous shuyūkh of the tarīqah as a result of their ijtihād on the practice of ‘uzlah and khalwah practiced by the Prophet SAW. The practice of sulūk includes some specific practices and manners that must be followed by each salik to achieve the main goal of ma‘rifatullah. Although the practice of sulūk has long been practiced by most communities in the Archipelago, but the participation of women is still at a moderate level compared to men. Women are the majority population in the world and are increasing in number from time to time. Although they are said to have a longer life expectancy than men, it does not guarantee lasting happiness and health. They are often associated with various health problems including mental problems which eventually cause them to lose judgment and tend to do negligence things. Therefore, this study will focus on identifying the role of sulūk towards women practitioners of the Tarekat Naqsyabandiyyah Khalidiyyah at the Institut Latihan Ilmu Tarekat (ILIT) Manarah. This study uses a qualitative method by interviewing six female informants who are also among sulūk participants. The results of this study found that sulūk is effective in: 1) Providing peace of mind; 2) Preventing from doing things that are prohibited; 3) Making easier to remember God; and 4) Facilitating a person to self-reflection. In conclusion, sulūk is seen as an alternative method for women in finding solutions to problems that arise especially regarding mental health problems.